Analisis Konseptual Fenomena Fisika pada Lopi Sandeq Berbasis Studi Literatur untuk Pembelajaran - Mawardi Jalil Masri; Juniar Rasyid; Nurul Amalia Aris; Sulfianty; Afdalia (Jurnal Pendidikan dan Ilmu Fisika, 2025)
This study aims to examine the physical phenomena at work in the Lopi Sandeq through a conceptual analysis based on a structured literature review as a foundation for developing contextual and ethnoscience-oriented physics learning resources. The Lopi Sandeq was selected as the object of investigation because it is a traditional boat of the Mandar people known for its remarkable speed and stability, thus embodying various physics principles that can be explained systematically. The research employed a qualitative method using a structured literature review approach to analyze scholarly sources related to traditional boat design, fluid mechanics, sail aerodynamics, object motion dynamics, and learning theories rooted in local wisdom. The analysis was conducted through the identification, categorization, and synthesis of findings from relevant references. The results indicate that the design and performance of the Sandeq represent implementations of physical principles such as buoyant force, rotational stability, fluid dynamics, aerodynamic lift on sails, momentum, impulse, and mass distribution equilibrium. Its slender hull shape minimizes wave drag, while the outrigger provides stabilizing torque to maintain balance. The sail system combines thrust and lift forces to generate efficient acceleration. Beyond its scientific contributions, the study reveals that the Sandeq has significant potential as a physics learning medium based on ethnoscience, offering real-life contexts closely connected to students’ sociocultural environments. The study concludes that analyzing the physical phenomena of the Sandeq can enrich conceptual understanding of physics while strengthening cultural literacy within the learning process.